The souvenir and its organization from the relationship with the cultural identity - Charpentier, Claudio Andrés Petit-Laurent (2017)
In the following lines we will raise an analysis of the relationship established between the souvenir objects, understood as design objects whose meaning lies in its symbolic and conceptual, as containers of the idea of memory, and the cultural context in which They offer and intended to communicate a number of meanings attached to their identity. The analysis will be based on a definition bounded to the idea of culture and cultural identity as a dynamic conceptual construct contingent in the context of post-modernity and therefore will be decisive in generating categories on which to propose a classification or organization of these objects.